The influence of ZIS fund distribution, social aid shopping, and subsidy shopping to poverty in Indonesia - Nurul Ichsan Hasan; Nurul Mudhiatil Mufliha (Indonesian Journal of Islamic Economics Research, 2020)
Indonesia has 10 percent of the poor population. Getting rid of that poverty gap, instruments that have been made are needed. One of the instruments is the distribution of ZIS funds by the National Amil Zakat Agency (BAZNAS), then spending aid social services by the central government, and subsidy spending by the central government. Then with this poverty problem, the importance of emphasizing the distribution of ZIS funds in Indonesia, spending on social assistance, spending on subsidies, and research on poverty. This study aims to analyze the effect of ZIS funds distribution, Social Aid Expenditures, and Subsidy Expenditures on poverty in Indonesia in the 2013-2017 period. The sample of this study consisted of 4, namely ZIS data obtained at the National Amil Zakat Agency (BAZNAS), then spending on social aid, expenditure on subsidies, and finally, data on poverty obtained from the Central Statistics Agency (BPS). The method used is a quantitative method by testing the classical assumptions. The results of this study are according to the results of the F test that the three independent variables (ZIS, Social Aid, and Subsidies) simultaneously influence the dependent variable (poverty).